2006
DOI: 10.1063/1.2392816
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of a single molecule anchored by an isocyanide substituent to gold electrodes

Abstract: The effect of anchoring group on the electrical conductance of a single molecule bridging two Au electrodes was studied using disubstituted [isocyanide (CN–), thiol (S–), or cyanide (NC–)] benzene. The conductance of a single Au/1,4-diisocyanobenzene/Au junction anchored by isocyanide via a C atom (junction with the Au–CN bond) was 3×10−3G0(=2e2/h). The value was comparable to 4×10−3G0 of a single Au/1,4-benzenedithiol/Au junction with the Au–S bond. The Au/1,4-dicyanobenzene/Au molecular junction with the Au–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 18 publications
4
117
1
Order By: Relevance
“…The single-molecule junction we study here is non-metallic, and the electrical resistance is expected to be much higher than that of the Au/1,4-dicyanobenzene/Au junction (6.47 MO) 3,43 . Following the interfacial Wiedemann-Franz law that relates interfacial electrical conductance to its electrical thermal conductance k e (ref.…”
Section: Discussionmentioning
confidence: 99%
“…The single-molecule junction we study here is non-metallic, and the electrical resistance is expected to be much higher than that of the Au/1,4-dicyanobenzene/Au junction (6.47 MO) 3,43 . Following the interfacial Wiedemann-Franz law that relates interfacial electrical conductance to its electrical thermal conductance k e (ref.…”
Section: Discussionmentioning
confidence: 99%
“…1(a)). Details on the experimental design used in this study have been previously reported by our group [6][7][8][9]. The STM tip was made of an Au wire (diameter ~0.25 mm, >99 %).…”
Section: Methodsmentioning
confidence: 99%
“…In order to compare the conductance of the single molecular junction with different end group position, the conductance of the single molecular junction should be precisely determined. Generally, the conductance of the single molecular junction could vary with the experimental condition [6]. The minimization of the variability of the conductance values is critically important in the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the combination of thiol (SH) and Au electrodes, a variety of anchoring groups has been investigated, such as pyridine, 4 isocyanide, 5,6 carboxylate, 7 selenide, 8 amine, 913 phosphine, 14 C 60 , 15 and carbon 16,17 for various electrodes. In this study, we explored the possibility of using a phosphine sulfide (P=S) bond as a new anchoring group to form single molecule junctions with Au electrodes.…”
mentioning
confidence: 99%